Accountability in development national and international - Nehru, B.K...[et al] (New Delhi, 1982)
Accountability in Development is a collection of papers presented at a seminar sponsored by the Leslie Sawhny Programme, and attended by eminent personalities-ministers of cabinet rank from Sri Lanka and Sudan, members of parliament from India, distinguished civil servants with experience, noted administrators, economists, industrialists and management experts.
Keywords: Public administration